Histoid Leprosy - Karthikeyan, Kaliaperumal (Am J Trop Med Hyg, 2015)
Histoid leprosy is rare type of lepromatous leprosy characterized by unique clinical, histopathological, and microbiological features. It is characterized by cutaneous and subcutaneous nodules. Histoid leprosy cases represent probable resistant bacilli and a highly active lepromatous process. These cases may act as reservoirs of the disease and lead to further spread of leprosy. Continual occurrence of these cases does not bode well for eradication of leprosy.